2014
DOI: 10.1118/1.4896820
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of atrial radio frequency ablation using intracardiac shear‐wave elastography

Abstract: By its quantitative and real-time capabilities, Intracardiac SWE is a promising intraoperative imaging technique for the evaluation of thermal ablation during RFCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…Other imaging modalities that were explored for ablation lesion monitoring are conventional ultrasound [12][13][14][15] as well as ultrasound elastography [16][17][18]. Visibility of lesions on grayscale ultrasound has been disputed in literature, with contradictory reports of both decrease and increase in echogenicity in lesion areas.…”
Section: Rf Ablation Lesion Imaging In the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Other imaging modalities that were explored for ablation lesion monitoring are conventional ultrasound [12][13][14][15] as well as ultrasound elastography [16][17][18]. Visibility of lesions on grayscale ultrasound has been disputed in literature, with contradictory reports of both decrease and increase in echogenicity in lesion areas.…”
Section: Rf Ablation Lesion Imaging In the Literaturementioning
confidence: 99%
“…Elastography, on the other hand, seems more successful at lesion identification and looks quite promising. However, monitoring lesion progression with shear wave elastography is still a challenge due to the estimation of atrial wall curvature for wave propagation progression and the difficulty in aligning the ultrasound beam to the lesion site across the ablation catheter [18].…”
Section: Rf Ablation Lesion Imaging In the Literaturementioning
confidence: 99%
“…Nevertheless, multiple groups have now shown that deformability as indexed by these techniques drops immediately following RF ablation in vivo. (Bahnson et al, 2014; Kwiecinski et al, 2014) Interestingly, this shear stiffness is quite stable from 2-30 minutes after ablation in the center of the lesion, while the stiffness of adjacent myocardium increases more slowly; (Eyerly et al, 2015) Eyerly et al suggested that the immediate response may reflect changes in tissue properties due to thermal damage, while the slower response in adjacent tissue reflects edema. (Eyerly et al, 2015) Less is known about the evolution of mechanical properties beyond the first few minutes post-ablation, other than the fact that scar tissue forms in damaged regions and is presumably stiffer than the surrounding myocardium.…”
Section: Ablation Of Atrial Fibrillationmentioning
confidence: 99%
“…In order to visualize the thermal lesion with ultrasound, evaluation of tissue stiffness has recently been introduced as an effective means to map ablated regions [3][4][5][6][7], providing stiffness contrasts between normal and ablated tissues of more than a factor of 2. It was shown in vivo that the stiffening of a thermally ablated tissue is linked to the applied thermal dose [8], and thus, to its viability.…”
Section: Introductionmentioning
confidence: 99%